Status stvarnosti v sodobni sociologiji medicine - Kuran, Manuel (Družboslovne razprave, 2008)
The author discusses the ontological and epistemological directions of the contemporary sociology of medicine, which are primarily manifested in relation to the socalled primary world or reality. The main topic of discussion is the concept of mental illness due largely to its strong presence in social theory and its very complex nature. Current questions and concerns arising from the findings of modern cognitive science are presented through a historical overview of four sociological writers - Durkheim, Parsons, Foucault and Szasz - and a critical analysis of three dimensions of the social constructionism paradigm. The whole discussion is placed, for this is the main goal of this scientific contribution, within a wide framework of interdisciplinary means between the sociology of medicine, cognitive science and natural science.
Keywords: Medical sociology; Sociologija medicine; Epistemologija; Epistemology; Duševne bolezni; Mental illness; Sociological theories; Sociološke teorije; Cognitive science; Kognitivna znanost; stvarnost